Exploring the Mediating Role of Executive Function in the Relationship between Aerobic Fitness and Academic Achievement in Adolescents - Seyun Park; Haeyong Chun; Jennifer L. Etnier; Daehyun Yun (Brain Sciences, 2023)
(1) Background: The performance of physical activity at a sufficient volume can result in improvements in fitness. Aerobic fitness is a particular aspect of fitness that has consistently been shown to be related to both cognitive performance and academic achievement. Cognitive performance, particularly executive function, is itself predictive of academic achievement. It has been hypothesized that the benefits of aerobic fitness for academic achievement are due to improvements in executive function. This study explores the mediating role of cognitive performance on the relationship between physical fitness and academic achievement in high-school-aged adolescents. (2) Methods: High school students (N = 283, 127 male, 156 females, mean age = 16.05 years, SD = 0.41) performed a shuttle run test to assess aerobic fitness and completed the Stroop Color, Stroop Word, and Stroop Color–Word tests to measure information processing and inhibition. They also completed the National Union Academic Achievement Assessment (NUAAA) as part of their high school requirements. (3) Results: Mediation analyses showed that inhibition (performance in the Stroop Color–Word test) fully mediated the relationship between aerobic fitness and both mathematics and Korean performance. (4) Conclusions: This cross-sectional investigation suggests an important mediating role of cognitive performance related to executive function in understanding the relationship between aerobic fitness and the academic achievement of high-school-aged adolescents. This suggests that enhancements in performance related to executive function, which are attributed to increases in aerobic fitness, could explain the observed benefits for academic attainment.